Skin wound healing part II: from traditional cataplasm to advanced wound dressings - Romero, Amanda Guadalupe; Rodriguez, Andrea Paola; Kozuszko, Silvia Noemi; Nagano, Kenichi; Felice, Carmelo José; Katase, Naoki (Frontiers in Soft Matter, 2026)
The first part of this review summarizes fundamental wound-healing biology and advances a novel, integrative roadmap for developing next-generation wound technologies that weave together ancestral knowledges and modern biomaterials science, analyzing recent evidence and translational opportunities in that direction. It also examines clinical trials, patents, regulatory issues, and epistemological challenges around medicinal plants. (DOI). This second part delves into historical poultices and the plants used to make them, summarizing reported medicinal effects, key phytochemicals, and mechanisms for topical wound and inflammation modulation. It follows the translation of these materia medica into modern technologies identifying translational routes and technical gaps. In addition, the review examines the validation of medicinal products integrated into modern technological platforms, encompassing in vitro assays, in vivo experiments, and clinical trials. The paper argues that ancestral health paradigms, rooted in ecological knowledge and community practice, can complement biomedical frameworks across research, product design, and clinical use. It prioritizes respectful, participatory approaches that conserve biodiversity and protect the intellectual and cultural rights of source communities while centering patient autonomy and psychosocial support. Finally, it calls out critical evidence gaps and proposes methodological, ethical, and regulatory standards for rigorous ethnopharmacological validation and responsible integration of traditional poultice knowledge into contemporary wound-care innovation.